Penggunaan Media Ritatoon untuk Meningkatkan Pengetahuan Seksual Anak Usia Dini - Amanda, Yosi Nur Annisa; Indryani, Indryani; Utami, Winda Sherly (Nusantara: Jurnal Pendidikan Indonesia, 2024)
Purpose – Knowledge of sexuality is crucial from an early age because it can help children avoid sexual harassment and prevent gender bias. This study aims to find out whether Ritatoon media can affect sexual knowledge of children aged 5 to 6 years in PAUD Melati 2 in Jambi City.Method – The research was conducted using a pre-experimental design of One-Group Pretest-Posttest Design, total sampling, and a non-probability approach, purposive sampling type. The data analysis techniques used included t-test hypothesis testing with prerequisite tests of homogeneity and normality..Findings – The research results show that the average pre-test score is 15.111 and the average post-test score is 21.889 with a total score of 197. The t test results show that the value of t count is 30,500, which is the same as the t table of 2.365, so t count > t table shows that there is The influence is on strong interpretation with a value of 3.17 which is in the range > 1.00 with strong interpretation (Strong Effect). Calculated results showed that the average pre-test score was 15.111 with a total score of 136, and the average post-test score was 21.889 with a total score of 197. The average final test score was higher than the average initial test score of 6.778, which shows that Ritatoon media has an impact on children's sexual educationResearch Implications – The study's findings suggest that ritatoon media can be utilized as a teaching tool to help kids between the ages of five and six build their sexual literacy by giving them more insight into and information about learning activities that can help them become more sexually knowledgeable. via media and education, and serve as a resource for educators doing exercises aimed at promoting early sexual education.